Preferential Homing of Tumor-specific and Functional CD8+ Stem Cell-like Memory T Cells to the Bone Marrow. Issue 6 (July 2019) - Wu, Kang; Li, Yongchao; Zhang, Shaoying; Zhou, Nan; Liu, Bingfeng; Pan, Ting; Zhang, Xu; Luo, Haihua; Huang, Zhaofeng; Li, Xuefeng; Zhang, Hui; Zhang, Junsong
Abstract : The bone marrow (BM) harbors not only hematopoietic stem cells but also conventional memory T and B cells. Studies of BM-resident memory T cells have revealed the complex relationship between BM and immunologic memory. In the present study, we identified CD122 high stem cells antigen-1 (Sca-1) high, B-cell lymphoma protein-2 (Bcl-2) high, CD8 + stem cell-like memory T cells (TSCM s) as a distinct memory T-cell subset preferentially residing in the BM, where these cells respond vigorously to blood-borne antigens. We found that the most TSCM s favorably relocate to the BM by adhesion molecules such as vascular cell adhesion protein 1, P-selectin glycoprotein 1, and P-selectin or E-selectin. Moreover, the BM-resident TSCM s exhibited much higher levels of antitumor activity than the spleen-resident TSCM s. These results indicate that the BM provides an appropriate microenvironment for the survival of CD8 + TSCM s, thereby broadening our knowledge of the memory maintenance of antigen-specific CD8 + T lymphocytes. The present findings are expected to be instructive for the development of tumor immunotherapy. Abstract : Supplemental Digital Content is available in the text.